Pemanfaatan Canva oleh Mahasiswa IPII untuk Mengemas Ulang Informasi Literasi Digital ke dalam Bentuk Infografis - Muhammad Rizky; Fadira Az-zahra; Malika Fitriazara (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
The development of information technology has driven the need for digital literacy skills that include not only technical aspects, but also critical thinking skills, visual communication, and digital ethics, which are very relevant for students. This study aims to explore the use of Canva as a means to redesign digital literacy information into infographic format by students of the Islamic library and information science (IPII). The method applied is descriptive qualitative with data collection through semi-structured interviews and observations. The findings of this study show that students can combine digital literacy content with attractive and communicative visual designs using Canva. Despite facing several obstacles such as limited premium features and dependence on internet connections, students still feel that Canva is an efficient and easy-to-use tool. This study emphasizes the importance of strengthening the curriculum that combines digital literacy and visual design to support students' communication skills in the digital era. The practical implications of this study encourage universities to provide training on infographic design and access to technology-based design platforms.